The Role of Al-Khalil Ibn Ahmad Al-Farahidi in Arabic Lexicography (Mu'jam Al-'Ain) - Wijaya, Ahmad Ardiyanto; Karima, Dewi Sofiyatul (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2023)
The first dictionary in the world was a dictionary compiled by al-Khalil. Al-Khalil's thoughts as an Arabic linguist are outlined in the Book of al-'Ain as a manifestation of his intelligence and analytical sharpness, so that he is able to explain and innovate. The contents of the opening of the dictionary of al-'Ain explain the function of letters in word formation. Al-Khalil groups words based on their volume, from smallest to largest. The vocabulary of the Al-'Ain dictionary is also sorted based on its phonetic aspects (makharij al-huruf). Apart from that, there were also differences of opinion regarding the first compiler of this book, resulting in various contradictions. The reason this research was conducted was to find out and uncover the ins and outs of the composition of mu'jam al-'Ain. The method used in this research is qualitative which is carried out by reducing and simplifying the data and then presenting and narrating the conclusions to provide an explanation of the core of the research carried out by the researcher. The results of this analysis show that mu'jam al-'Ain written by the pioneer of mu'jam, namely al-Khalil al-Farahidi, groups words based on the number of letters, namely from tsuna'i, tsulatsi, ruba'i, and khumasi. Al-Khalil compiled the vocabulary by ordering it according to the makharij al-huruf that he explained in his opinion, then turning the entries upside down, because the hamzah letters are letters that come out of the larynx. Apart from that, in each vocabulary there are several explanations related to sharfiyah and nahwiyah.